O papel da sumoilação de proteínas na biologia celular de giardia lamblia - Genova, Bruno Martorelli Di [UNIFESP] (2016)
Protein post-translational modification (PTM) increases the functional diversity of the proteome by the covalent addition of functional groups or proteins. PTMs include the bonding of a chemical group (acetyl, methyl), modifications of amino acids (deamination, elimination), addition of more complex molecules like sugars (glycosylation), lipids (isoprenylation) or another protein. In the latter case, ubiquitination (addition of an ubiquitin) and SUMOylation (addition of a SUMO) are well known PTMs occurring in eukaryotic cells. Modification of a protein by SUMO (Small Ubiquitin-like MOdifier) is known to play a role in many cellular processes such as nuclear-cytoplasmic transport, transcriptional regulation, progression through cell cycle, protein stability and protein cellular localization. In this thesis the biological role of protein SUMOylation was investigated in Giardia lamblia and the data herein show that Giardia genome contains a single SUMO gene, codifying for a SUMO protein (GlSUMO) with 42,7 % identity with the human SUMO-1. In trophozoites GlSUMO is localized mainly at the cell cytoplasm, but also in the nuclei, the perinuclear region and at the cell periphery where it co- localizes with VSPs, suggesting a possible role for SUMOylation in antigenic variation. Silencing of of GlSUMO by RNA interference resulted in trophozoites with abnormal morphologies, adhesion-deficient and slower growth rates. Compared to wild type parasites Flow cytometry and EdU assays suggest that cells with silenced expression of GlSUMO arrest in the G1/S transition. Moreover, the levels of transcripts for cyclin B and ?-giardin are reduced in trophozoites GlSUMO depleted. Ablation of GlSUMO also interfered in encystment, RNAi GlSUMO trophozoites produces less cyst, also the cysts with silenced expression of GlSUMO present deformed cyst walls. CMGC kinase, malate dehydrogenase, glycil t-RNA synthetase, uridine kinase, actin, poly-A polymerase, Lek 1, dnaJ chaperone, elongation factor 2 and arginine deiminase were identified as possible GlSUMO susbtrates by immunoprecipitation with anti-GlSUMO antibody and mass spectrometry. The present study provides strong evidence for a role for SUMO in the regulation of genes involved in cell cycle and cell architecture in Giardia lamblia and has revealed a potential mechanism for SUMO-mediated growth arrest.